Informatics in Control, Automation and Robotics Revised and Selected Papers from the International Conference on Informatics in Control, Automation and Robotics 2010 - Cetto, Juan Andrade; Ferrier, Jean-Louis; Felipe, Joaquim; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
The present book includes a set of selected papers from the seventh "International Conference on Informatics in Control Automation and Robotics" (ICINCO 2010), held in Madeira, Portugal, from 15 to 18 June 2010. The conference was organized in three simultaneous tracks: "Intelligent Control Systems and Optimization", "Robotics and Automation" and "Signal Processing, Systems Modeling and Control". The book is based on the same structure.   ICINCO received 320 paper submissions, not including those of workshops or special sessions, from 57 countries, in all continents. After a double blind paper review performed by the Program Committee only 27 submissions were accepted as full papers and thus selected for oral presentation, leading to a full paper acceptance ratio of 8%. Additional papers were accepted as short papers and posters. A further refinement was made after the conference, based also on the assessment of presentation quality, so that this book includes the extended and revised versions of the very best papers of ICINCO 2010.   Commitment to high quality standards is a major concern of ICINCO that will be maintained in the next editions of this conference, including not only the stringent paper acceptance ratios but also the quality of the program committee, keynote lectures, workshops and logistics
Invited Papers -- Part I: Intelligent Control Systems and Optimization -- Part II: Robotics and Automation -- Part III: Signal Processing, Systems Modeling and Control
Electronic reproduction
Keywords: Automatic control -- Congresses; Automation -- Congresses; Robotics -- Congresses